Hypolipidemic properties of the extracts of Belamcanda chinensis leaves (BCLE) in KK-A y mice - Ying Guo; Rongji Dai; Yulin Deng; Lili Sun; Shiying Meng; Nian Xin (Universidade de São Paulo, 2022)
Abstract The extract of Belamcanda chinensis leaves (BCLE) is a traditional Chinese herbal medicine for the treatment of diabetes-related hyperlipidemia in Hainan province, South China. In this study, the lipid-decreasing effects of BCLE on obese diabetes were investigated on KK-Ay mice. The component F2 ameliorated lipid disorder, as indicated by decreased levels of body weight, liver index, levels of TC, TG and LDL-c in the serum and liver. The enhancement effect of F2 on liver SOD and the inhibitory effect of F2 on MDA demonstrated that F2 exhibited significant antioxidant activity on liver injury. F2 also prevented vacuolar degeneration and reduced pathological tissue injury in liver. In addition, the component F1 decreased the levels of TG, LDL-c and MDA in the liver. These findings suggest that F2 may have therapeutic potential in the prevention and therapy of hyperlipemia and liver disease associated with obesity-related diabetes.